DEFINITE INTEGRAL (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article provides detailed information about the definite integral, the main properties of the definite integral,the calculation of the definite integral, the Newton-Leibnis formula, the calculation of the surfaces of flat figures using the definite integral, and the applications of the definite integral in economics.Ushbu maqolada aniq integral, aniq integralning asosiy xossalari, aniq integralni hisoblash, Nyuton-Leybnis formulasi, aniq integral yordamida yassi figuralar yuzalarini hisoblash va aniq integralning qoʻllanilishi haqida batafsil maʼlumotlar berilgan. iqtisodiyotda ajralmas.В этой статье приведены подробные сведения о определенном интеграле, основных свойствах определенного интеграла, вычислении определенного интеграла, формуле Ньютона-Лейбниса, расчете поверхностей плоских фигур с помощью определенного интеграла и приложениях определенного интеграла. неотъемлемая часть экономики.